Mental Health Needs and Service Utilization by Hispanic Immigrants Residing in Mid-Southern United States - Bridges, Ana J. (2012)
PURPOSE: This study assessed mental health needs and service utilization patterns in a convenience sample of Hispanic immigrants. DESIGN AND METHOD: A total of 84 adult Hispanic participants completed a structured diagnostic interview and a semistructured service utilization interview with trained bilingual research assistants. RESULTS: In the sample, 36% met diagnostic criteria for at least one mental disorder. Although 42% of the sample saw a physician in the prior year, mental health services were being rendered primarily by religious leaders. The most common barriers to service utilization were cost (59%), lack of health insurance (35%), and language (31%). Although more women than men met criteria for a disorder, service utilization rates were comparable. Participants with a mental disorder were significantly more likely to have sought medical, but not psychiatric, services in the prior year and faced significantly more cost barriers than participants without a mental disorder. CONCLUSIONS: Findings suggest that Hispanic immigrants, particularly those with a mental illness, need to access services but face numerous systemic barriers. The authors recommend specific ways to make services more affordable and linguistically accessible.